The mediatrician's guide : a joyful approach to raising healthy, smart, kind kids in a screen-saturated world - Rich, Michael Professor of Pediatrics; Barker, Teresa (Harper Horizon, 2024)
"Dr. Michael Rich, dubbed the 'Mediatrician' thanks to his acclaimed work as a pediatrician, child health researcher, and children's media specialist, offers a science-backed approach to give parents the confidence they need to raise a child well (and to raise a well child) in the digital age." -- Publisher annotation.